O2E.4 Evaluation of exposure assessment methods in epidemiological studies: the welding example. (April 2019) - Peters, Susan; Lavoue, Jerome; Baker, Marissa; Kromhout, Hans
Abstract : Exposure assessment quality is a fundamental consideration in the design and evaluation of observational studies. High quality exposure assessment is particularly relevant for outcomes with long latency, such as cancer, where detailed information on past exposures are often missing and must therefore be estimated. For the IARC Monograph on welding, the exposure group provided an overview of assessment methods used in the key epidemiological studies. Strengths and weaknesses of each study were assessed, along with their potential effects on interpretation of risk estimates. For the association between lung cancer and welding fume exposure, 9 cohort and 10 case-control studies were reviewed. For ocular melanoma and ultraviolet radiation (UVR) from welding, 7 case-control studies were reviewed. Quality criteria were: full occupational histories, and standardized, blinded and quantitative exposure assessment. Additional criteria for lung cancer: specifically assessing welding fumes and using information on welding tasks. For ocular melanoma: assessing artificial and solar radiation separately, taking into account eye burns, eye protection and welding type. Exposure assessment of welding fumes by applying a 'welding-exposure matrix' (n=2) or welding-specific questionnaires (n=3) were considered highest quality, followed by case-by-case expert assessment (n=5) or general job-exposure matrices (JEMs, n=4). Job title alone was considered less informative (n=5). For exposure to UVR, JEMs were most informative (n=2), followed by self-reported eye burns and self-reported exposure from specific welding types (n=2), although caution is advised regarding recall bias. Assessing welding fume exposure or ever exposure to welding arcs as proxy for UVR was considered less informative. For both exposures, ever versus never welder, or assessments based on data collected from proxies, were considered least informative. The overall evaluation was that there is sufficient evidence in humans for the carcinogenicity of welding fumes and ultraviolet radiation from welding.